Non-equilibrium landscape and flux reveal how the central amygdala circuit gates passive and active defensive responses. Issue 153 (10th April 2019) - Yan, Han; Li, Bo; Wang, Jin
Abstract : Uncovering the underlying physical principles of biology is important for understanding the biological function yet challenging. Take an example, the animals' defensive systems are very effective to threats. However, the underlying physical mechanisms are still unclear. We developed a non-equilibrium physics framework in terms of landscape and flux to study a central lateral amygdala (CeL) neural circuit based on experimental findings. We show that the distinct active and passive defensive responses of the animals upon threats are a result of non-equilibrium phase transitions. Such non-equilibrium phase transitions result from thermodynamic symmetry breaking, which is induced dynamically by the non-equilibrium flux. This gives rise to the emergence and selection of passive and active fear defensive responses, which can be quantified by the changes on the topography of the underlying non-equilibrium landscape. We have found the strengthened synaptic transmissions to both the SOM + and SOM − CeL neurons are necessary for the acquisition and expression of active fear responses. This suggests a way to induce active responses and facilitates the design of new therapeutic strategies for cognitive dysfunction. We have also found that sufficient energy supply is crucial for the ability of selecting the appropriate defensive responses through stabilizing functional states against fluctuations.